2017
DOI: 10.1103/physrevlett.118.123002
|View full text |Cite
|
Sign up to set email alerts
|

Enantiomer-Specific State Transfer of Chiral Molecules

Abstract: State-selective enantiomeric excess is realized using microwave-driven coherent population transfer. The method selectively promotes either R or S molecules to a higher rotational state by phasecontrolled microwave pulses that drive electric-dipole allowed rotational transitions. We demonstrate the enantiomer-specific state transfer method using enantiopure samples of 1,2-propanediol. This method of state-specific enantiomeric enrichment can be applied to a large class of asymmetric, chiral molecules that can … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
264
0
7

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 154 publications
(277 citation statements)
references
References 21 publications
6
264
0
7
Order By: Relevance
“…Very recently,i tw as demonstrated that this technique can also be extended to achieve enantiomer-selective population transfer. [24,25] Here, we report our resultso fahigh-resolution broadband rotational spectroscopy study on the monoterpene pulegone (2-isopropylidene-5-methylcyclohexanone, see Figure1 below) in the gas phase, which provides information on the isolated speciesf ree of solvent effects. Pulegone can be found in many plants.…”
Section: Introductionmentioning
confidence: 94%
See 3 more Smart Citations
“…Very recently,i tw as demonstrated that this technique can also be extended to achieve enantiomer-selective population transfer. [24,25] Here, we report our resultso fahigh-resolution broadband rotational spectroscopy study on the monoterpene pulegone (2-isopropylidene-5-methylcyclohexanone, see Figure1 below) in the gas phase, which provides information on the isolated speciesf ree of solvent effects. Pulegone can be found in many plants.…”
Section: Introductionmentioning
confidence: 94%
“…The twist pulse durations should fulfill p pulse conditions. [47] The p twist pulse transfers coherence from the 5 24 ! 5 14 (induced by the p/2 drive pulse) to the 5 14 !…”
Section: Enantiomer Differentiationu Sing M3wmmentioning
confidence: 99%
See 2 more Smart Citations
“…Since the early days of Otto Stern [1] and Immanuel Estermann, [2] neutral molecular beams have played a key role in fundamental studies of physics and physical chemistry. [3][4][5] Experiments with isolated molecules in the gas phase have laid the ground for highprecision spectroscopy, [6,7] molecule and cluster deflectometry [8][9][10] and for an improved understanding of chemical reactions with quantum state control. [11,12] Modern molecular beam experiments have allowed setting new bounds on the electric dipole moment of the electron [13,14] and enabled the observation of quantum interference with clusters and molecules, [15,16] even with masses exceeding 10 0 000 amu.…”
Section: Introductionmentioning
confidence: 99%